Marketing Communication Strategies of Pentol Kluwung Reviewed From SOSTAC Analysis: Situation, Objective, Strategy, Tactics, Action, Controlling - Leonard Adrie Manafe; Yovita Ardeana; Kori Pramita; Femmy Roszalinda Marteza Leo (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpose: This study aims to determine the marketing communication strategy used by Pentol Kluwung through Instagram media. Design/methodology/approach: The type of research used is descriptive qualitative method. The non random sampling technique (purposive sampling) used direct communication by involving 30 informants. Findings: The results of this study indicate that Pentol Kluwung uses several marketing communication strategies by implementing SOSTAC (Situation, Objective, Strategy, Tactics, Action, Controlling) then promotional communication strategies through Instagram media to convey product information in the form of visuals, audio and messages. Research limitations/implications: The limitation of this research is about the gender comparison of the informants. The number of informants with gender characteristics is not comparable. Researchers get female dominant informants; this can be a reference for future researchers. Practical implications: Important implications found in this research activity are in order to be able to further improve the quality of Pentol Kluwung products. Originality/value: The paper is original. Paper type: Research paper